Identification of Unique Subgenotype Specific Pattern (USSP) in nucleocapsid protein of new novel NDV VIIj (VII.1.1) - Esmaelizad, Majid; Naghshbandi, Parzhin; Esmaelizad, Nazanin (Journal of BioScience and Biotechnology, 2021)
Newcastle disease virus (NDV) is one of the most prominent, dangerous, and transmittable viral diseases in birds. Nucleocapsid protein plays an important role in the duplication and assembly of viruses. It also has an antigenic role. In this study, we attempted to molecular characterization of the complete coding sequence of nucleocapsid gene of the novel highly pathogen subgenotype VIIj (VII.1.1) isolates in Iran. For amplification and sequencing of NP complete coding sequence, three forward and two reverse degenerated primers were designed. After RT-PCR followed sequencing, the nucleotide sequences were compared to all other 120 sequences registered in the GenBank. Two novel amino acid substitutions I403àV and N432àG were identified in this subgenotype among all of NP sequences from two classes and eighteen genotypes of ND Viruses available in DATA bases. These new highly pathogen isolates of Iran located in distinct groups closely related to subgenotype VIId with more than three percent divergence. Two other unique amino acid substitutions T426àA and P464àS were identified compare to subgenotype VIId. New profiles in B-cell and T-cell epitopes were observed in the NP protein of NDV-VIIj. It seems that in addition to known virulence factors, these amino acid substitutions in NP protein during virus evolution might be one of the reasons for increasing the virulence of new isolates or vaccine inefficiency.